Moot Court as Learning Method for Bachelor of Law: Towards Progressive Legal Education - Suartha, I Dewa Made; Martha, I Dewa Agung Gede Mahardhika (Kertha Patrika; Vol 42 No 2 (2020)DO - 10.24843/KP.2020.v42.i02.p01, 2020)
Moot court is onepractical learning method of procedural law learning that must be given to undergraduate law students. This learning method as a framework initiated by John Dewey as the achievement of progressive legal education, especially in criminal justice practices. The purpose of this learning method is to provide students with a deepening of criminal justice both based on theory and practice as well as provide opportunities for students to carry out the criminal trial practice by taking examples of criminal case decisions that have obtained permanent legal force. This paper specifically discovers, studies, analyzes and provides deepening related to criminal justice based on theory and practice for law students at the level of the Bachelor of Law program to obtain a progressive legal education The method used in this paper is empirical legal research method using primary data and secondary data based on a purposive sampling model with deep-interview concerning the practice of the moot court in law higher education. The results of this study indicate that students have gained a deepening of criminal procedural law, particularly in the implementation of criminal justice guided by supervisors and legal practitioners as tutors and instructors. This study also s uggested that students have been able to practice criminal justice as true as actual criminal trials accompanied by supervisors and legal practitioners as their mentors in achieving progressive legal education.